2022
DOI: 10.1177/00219983221098225
|View full text |Cite
|
Sign up to set email alerts
|

A laminated vitrimer composite with strain sensing, delamination self-healing, deicing, and room-temperature shape restoration properties

Abstract: Laminated multifunctional composites are highly desired in modern lightweight engineering structures. The purpose of this study is to develop a composite laminate with impact tolerance, delamination healing, strain sensing, Joule heating, deicing, and room temperature shape restoration functionalities. In this study, a novel self-healable and recyclable shape memory vitrimer was used as the matrix, unidirectional glass fabric was used as reinforcement, and tension programmed shape memory alloy (SMA) wires were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For example, Yan and Li (2020a) developed a four-chain model to describe the constitutive behavior of enthalpy-driven SMPs, which was also validated by molecular dynamics simulation (Wick et al, 2021). A recent development in amorphous SMPs is the combination of the shape memory effect and other functionalities, such as selfhealing and recycling capabilities within the framework of vitrimers (Montarnal, et al, 2011;Lu et al, 2012;Gandini, 2013;Denissen et al, 2015;Obadia, et al, 2015;Chao et al, 2016;de Luzuriaga, et al, 2016;Lu et al, 2017;Nishimura, et al, 2017;Rottger, et al, 2017;Feng et al, 2019;Yuan et al, 2019;Feng et al, 2020a;Feng and Li, 2020b;Konlan et al, 2020;Suslu et al, 2020;Feng and Li, 2021a;Feng and Li, 2021b;Feng and Li, 2021c;Feng and Li, 2022;Konlan et al, 2022), which seamlessly utilized the shape memory effect to close the wide-opened crack first and heal the closed crack by the adaptable covalent network (CAN), per the close-then-heal (CTH) strategy initiated in Li's lab (John and Li, 2010;Li and John, 2008;Li and Nettles, 2010;Li and Uppu, 2010;Nji and Li, 2010a;Nji and Li, 2010b;Nji and Li, 2012). The combination of the shape memory effect with flame retardancy is another new development (Feng et al, 2019;Feng et al, 2020a;Feng et al, 2020b;Feng and Li, 2021a;Feng and Li, 2021b;…”
Section: Figure 13mentioning
confidence: 99%
“…For example, Yan and Li (2020a) developed a four-chain model to describe the constitutive behavior of enthalpy-driven SMPs, which was also validated by molecular dynamics simulation (Wick et al, 2021). A recent development in amorphous SMPs is the combination of the shape memory effect and other functionalities, such as selfhealing and recycling capabilities within the framework of vitrimers (Montarnal, et al, 2011;Lu et al, 2012;Gandini, 2013;Denissen et al, 2015;Obadia, et al, 2015;Chao et al, 2016;de Luzuriaga, et al, 2016;Lu et al, 2017;Nishimura, et al, 2017;Rottger, et al, 2017;Feng et al, 2019;Yuan et al, 2019;Feng et al, 2020a;Feng and Li, 2020b;Konlan et al, 2020;Suslu et al, 2020;Feng and Li, 2021a;Feng and Li, 2021b;Feng and Li, 2021c;Feng and Li, 2022;Konlan et al, 2022), which seamlessly utilized the shape memory effect to close the wide-opened crack first and heal the closed crack by the adaptable covalent network (CAN), per the close-then-heal (CTH) strategy initiated in Li's lab (John and Li, 2010;Li and John, 2008;Li and Nettles, 2010;Li and Uppu, 2010;Nji and Li, 2010a;Nji and Li, 2010b;Nji and Li, 2012). The combination of the shape memory effect with flame retardancy is another new development (Feng et al, 2019;Feng et al, 2020a;Feng et al, 2020b;Feng and Li, 2021a;Feng and Li, 2021b;…”
Section: Figure 13mentioning
confidence: 99%
“…And the propagation is calculated by taking the difference between the maximum impact energy and the initiation energy. Thus, it can be deduced that, a large value of CIE and a small propagation energy suggest a high impact tolerance [63,64].…”
Section: Impact Test and Cai Test Resultsmentioning
confidence: 99%
“…The results of fatigue tests showed that each repair cycle produced almost complete recovery of bending strength and modulus. Konlan et al 92 developed a multifunctional composite laminate with high impact resistance, self‐healing ability, strain sensing, joule heating, de‐icing and room temperature shape recovery capacity. The epoxy vitrimer was used as the matrix and unidirectional glass fibers as the reinforcing fibers.…”
Section: Intrinsic Self‐healing Compositesmentioning
confidence: 99%